2004
DOI: 10.1136/bjsm.2002.002352
|View full text |Cite
|
Sign up to set email alerts
|

The Football Association Medical Research Programme: an audit of injuries in professional football—analysis of hamstring injuries

Abstract: Objective: To conduct a detailed analysis of hamstring injuries sustained in English professional football over two competitive seasons. Methods: Club medical staff at 91 professional football clubs annotated player injuries over two seasons. A specific injury audit questionnaire was used together with a weekly form that documented each clubs' current injury status. Results: Completed injury records for the two competitive seasons were obtained from 87% and 76% of the participating clubs respectively. Hamstrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
722
6
47

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 833 publications
(835 citation statements)
references
References 34 publications
39
722
6
47
Order By: Relevance
“…2 In English professional soccer players, 47% of match-play hamstrings strains were incurred during the final 15 minutes of each half. 3 The fatigue associated with soccer match play is specific to the characteristic activity profile. Soccer has an irregular and intermittent activity profile [7][8][9][10] and, thus, when considering soccer-specific fatigue, we should account for both physiologic and mechanical load.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 In English professional soccer players, 47% of match-play hamstrings strains were incurred during the final 15 minutes of each half. 3 The fatigue associated with soccer match play is specific to the characteristic activity profile. Soccer has an irregular and intermittent activity profile [7][8][9][10] and, thus, when considering soccer-specific fatigue, we should account for both physiologic and mechanical load.…”
mentioning
confidence: 99%
“…[1][2][3][4] In an epidemiologic study of English professional soccer athletes, the thigh was the most prevalent site for injury, with 81% of thigh injuries classified as muscular strains. 2 In US Major League Soccer, hamstrings strains incurred during matches and training sessions accounted for 42% of all strain injuries.…”
mentioning
confidence: 99%
“…It is believed that they often occur during rapid eccentric loading when they are stretched beyond the optimal torque for generating tension, notably during sprinting [52,58,60]. It has been suggested that eccentric exercise increases this angle of optimal torque and may reduce the risk of injury [61][62][63][64][65].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Hamstring strains are one of the most common injuries at professional football clubs, accounting for 12-16% of all injuries [5,39,58,59]. It is believed that they often occur during rapid eccentric loading when they are stretched beyond the optimal torque for generating tension, notably during sprinting [52,58,60].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Only a few sports, such as rugby present incidence rates that are higher than soccer [7,8]. It is important to note that in professional soccer, any injury sustained by a player inevitably is associated with, on the one hand, suffering for the player, but also an important economic loss for the club, with the ensuing repercussion in first level events to follow [9]. Despite the high injury rates, there is no consensus regarding the number or injuries or the underlying mechanisms [10,11].…”
Section: Introductionmentioning
confidence: 99%